Challenges facing multinational corporations (MNCs) in sustaining businesses within Iskandar Malaysia / Nur Melissa Mohammad Faisal Wee (Faculty of Business and Management, 2008)
Competing in an imperative liberalised environment, Malaysia needs to strengthen their core competencies in order to ensure that Malaysia continue to be an attractive place for investors especially Multinational Corporations (MNC).This research examines the challenges facing Multinational Corporations (MNC's) in sustaining businesses within Iskandar Malaysia. This study focuses on three independent variables which are Govemance Infrastructure, Transportation Infrastructure and Telecommunication Infrastructure. A sample of 30 MNC's in manufacturing sector located within Iskandar Malaysia has been tested to represent the population of MNC'S in manufacturing sector in this economic region. The method used in identifying the relationships between all variables is Frequency Testing, Cross Tabulation Testing and Correlation Testing. The result of the findings has identified that only Governance Infrastructure has significant relationships with challenges and the most influential factors among all the variables are also Governance Infrastructure.